Microplastics from mulching film is a distinct habitat for bacteria in farmland soil - Mengjun Zhang; Yanran Zhao; Xiao Qin; Weiqian Jia; Liwei Chai; MukeHuang; Yi Huang (Science of the Total Environment, 2019)
Microplastics, as an emerging pollutant of global importance, have been well documented in aquatic ecosystems. However, little is known about the effects of microplastics on agroecosystems, particularly for soil microbial com- munities. Herein, microplastics collected from cotton fields in Xinjiang, China, were analysed with a scanning electron microscope (SEM) and high-throughput sequencing to investigate the attached bacterial communities. Microplastic surfaces, especially pits and flakes, were colonized by various microorganisms, suggesting active hy- drolysis of plastic debris. The bacterial communities colonizing microplastics were significantly different in struc- ture from those in the surrounding soil, plant litter and macroplastics. In addition, statistical analysis of differentially abundant OTUs showed that microplastics serve as a “special microbial accumulator” in farmland soil, enriching some taxa that degrade polyethylene, such as Actinobacteria, Bacteroidetes and Proteobacteria. Co-occurrence network analysis revealed that the biotic interactions between microorganisms on microplastics are as complex as those in soil, and Acidobacteria, Chloroflexi, Gemmatimonadetes, and Bacteroidetes are consid- ered keystone species in bacterial communities. Collectively, the findings imply that microplastics acted as a dis- tinct habitat for bacteria in farmland soil, which increases our understanding of microplastic pollution.